Evaluation of the causes and diagnosis of acute hepatitis in children admitted to Tabriz Children Hospital - Babak Abdinia; Maryam Shoaran; Orang Abdollahi; Zahra Golchinfar (Journal of Research in Clinical Medicine)
Introduction: The hepatotropic viruses are the most common causes of hepatitis worldwide; however, other infectious and non-infectious reasons can play a role in disease progress. In this study, we examined the infectious and non-infectious causes, and diagnoses of clinical signs of acute hepatitis in children admitted to Tabriz Children Hospital. Methods: In this study, the files of the children hospitalized between 2006 and 2016 with acute viral and non-viral clinical signs were extracted in Tabriz Children Hospital and patients’ information including age, sex, place of residence, type of disease, and their recovery status were investigated. Results: Of all patients, 62 were boys (48.4%) and the mean age of the hospitalized children was 6.92±0.46 years. The most common cause was hepatitis A, followed by autoimmune hepatitis. There was no significant relationship between age, gender, and place of residence with diagnosis, but there was a significant relationship between diagnosis and hepatitis type. Conclusion: The most common type of hepatitis in our study was hepatitis A, and according to its method of transmission, observing health tips is of high significance. Based on the obtained results, autoimmune hepatitis is chronic and requires long-term follow-up.